Sekuritisasi Pengungsi dan Migran dari Timur Tengah oleh Pemerintah Hungaria Tahun 2015-2019 - Angga Nurdin Rachmat (Jurnal Ilmiah Hubungan Internasional, 2023)
The repressive policy issued by the Hungarian government has positioned refugees and migrants as threats to national security which has come under the spotlight of many parties including the European Union. Where in fact Hungary is a party state in the 1951 Refugee Convention and the 1967 protocol. This study sees that the behavior exhibited by Hungary is a form of securitization carried out on the issue of refugees and migrants by the Government of Viktor Orban. Therefore, this study seeks to uncover the processes and actors in securitization carried out by the Hungarian Government on refugees and migrants originated from the Middle East in the period 2015-2019. This research is based on a constructivism approach with securitization theory developed by the Copenhagen School to see the process and actors in the securitization of refugee and migrant issues by the Hungarian government. This study found that the securitization of the refugee and migrant issues in Hungary involving the activities of the speech act as a form of intersubjective communication aimed at building referent objects and shaping perceptions about threats from refugees and migrants carried out by PM Viktor Orban. Besides that, it was found that the mass media in Hungary became functional actors who contributed greatly to the success of the securitization process of refugee and migrant issues by becoming a bridge that connects securitizing actors and audiences. Keywords: Victor Orban; value; identity; threat; mass media